VARIABILITÉ PHÉNOTYPIQUE ET SÉLECTION DES CARACTÈRES AGRONOMIQUES DU BLÉ DUR (Triticum durum Desf.) SOUS CONDITIONS SEMI-ARIDES - Manel, Salmi; Leila, Haddad; Abdelmalek, Oulmi; Amar, Benmahammed; Abdelkader, Benbelkacem (European Scientific Journal, ESJ, 2015)
Genetic improvement of agronomic traits related to yield performance and adaptation to the production environments is conditioned by the presence of phenotypic variability of the targeted characters in the plant material subjected to selection. This research was conducted to assess the magnitude of phenotypic variability, the heritability and the expected genetic gain of selection of agronomic traits in 18 durum wheat (Triticum durum Desf) varieties and segregating lines. The results showed the presence of significant variability for the measured traits. The degree of genetic determination had values greater than 70% for the duration of the vegetative phase and plant height, and below 50% for yield and aboveground biomass. The expected genetic gain ranged from 4.8% for the duration of the vegetative phase to 45.9% for grain yield. Single-character selection identified 6 desirable genotypes which brought increases of 14.9% in harvest index, 3.7 g in 1000 kernel weight, 4.8% in relative water content, and declines of 18.6% in percent cells injury, 2.1 g in yield per plant, 2.1 cm in spike length, and 12.9 grains per spike, and a gain of 1.7 spikes associated to 8.8 g of biomass. Relatively to Bousselam, the check cultivar, the selected lines brought a grain yield advantage ranging from 53.8 to 161.5%. This yield gain is associated with a desirable improvement in heat stress tolerance, and an undesirable reduction in thousand kernel weight. The study of the